Características de carcaça e de carne de cordeiros alimentados com dietas contendo diferentes genótipos de cynodon - De Oliveira, Euclides Reuter; Monção, Flávio Pinto [UNESP]; Hostalácio, Afonso Nienkotter; Dos Santos, Mariana Viegas; Fernandes, Alexandre Rodrigo Mendes; De Araújo Gabriel, Andréa Maria; Da Graça Morais, Maria; Moura, Lais Valenzuela (My University, 2014)
This study aimed to evaluate body morphometry and qualitative traits of carcasses and meat of lambs in a feedlot, fed hay Cynodon genotypes: Jiggs, Vaquero, Tifton 68, Coast -Cross, Tifton 85 and Russel. The diets had forage to concentrate ratio of 60:40 for all levels of performance. The experimental design was a randomized block design with 6 treatments and 5 animals per treatment, randomly assigned according to body weight. There was no significant difference in slaughter weight, yield of carcass muscle and hot, with average values of 33.67 kg, 42.74 and 53.20%, respectively. There was a significant difference for heart girth and length of carcass, where the animals of the treatment Jiggs had greater in vivo measurements (78.40 and 67.60 cm, respectively). To the perimeter of leg, carcasses relating to Russel and Vaquero treatments had lesser extent. Lambs supplemented with hay Cynodon had potential for production of carcasses and meat quality.
Characteristics of housing and meat for lambs fed diets containing different genotypes cynodons
Keywords: Breeding system; Carcass yield; Fedlot; Forage; Sheep